Effect of diplacone on LPS-induced inflammatory gene expression in macrophages - Hošek, Jan; Müller Závalová, Veronika; Šmejkal, Karel; Bartoš, Milan (Folia biologica (Praha), 2010)
Flavonoids are commonly studied for their anti-inflammatory effects; however, this is the first paper describing the possible antiphlogistic activity of a geranylated flavanone. This study focused on the ability of diplacone to modulate the gene expression of pro-inflammatory tumour necrosis factor alpha and monocyte chemoattractant protein 1, and of anti-inflammatory zinc finger protein 36. The action of diplacone was also compared with that of conventional drug indomethacin. Human monocyte-derived macrophages of the human monocytic leukaemia cell line were pretreated with diplacone or indomethacin. Subsequently, inflammatory reaction was induced by lipopolysaccharide, and changes of tumour necrosis factor alpha, monocyte chemoattractant protein 1 and zinc finger protein 36 gene expression at the transcriptional level were measured. In this model, diplacone significantly down-regulated the expression of tumour necrosis factor alpha and monocyte chemoattractant protein 1 and up-regulated the zinc finger protein 36 expression. This makes diplacone a promising molecule for treatment of the inflammatory stage of diseases. The effect of diplacone in decreasing lipopolysaccharide-induced inflammatory gene expression is in many ways similar to that of the conventional drug indomethacin.
Keywords: Financing, Organized; Chemokine CCL2; lipopolysacharidy; flavonoidy; Tumor Necrosis Factor-alpha; Macrophages; Humans; lidé; financování organizované; molekulární struktura; makrofágy; Flavonoids; Lipopolysaccharides; chemokin CCL2; TNF-alfa; Cell Line; buněčné linie; Molecular Structure